Mobile and personal satellite communications 2 proceedings of the Second European Workshop on Mobile/Personal Satcoms (EMPS '96) - Vatalaro, F. (Francesco); Ananasso, F. (Fulvio) (Springer, 1996)
These conference proceedings cover such topics as satellite system architectures, multiple access, network and mobility managment, exploitation of KA and EHF bands, modulation and coding, business and service provision, and propagation channel characterization and modelling.